Analysis on Diverse Meanings of Good Governance Principles in Ten Relief Organizations - Ruuska, Katri (My University, 2009)
Good governance is a widely used term nowadays. The existence of good governance is important in the case of all sectors including the non-profit organizations, which are important actors in our society in many ways. Relief organizations, as a small but important part of non-profit organizations, are good example about the actors who are operating in the world, where the need for humanitarian help and development cooperation is growing all the time. The main interest of this study is focused on three following questions: 1) What kinds of meanings are relevant when three key principles of good governance (i.e. transparency, accountability, and efficiency) are put into practice in non-profit organizations, 2) how relief organizations, as part of non-profit organizations, understand these three principles of good governance, and 3) in which ways these principles are implemented in the actions of relief organizations. Thus, good governance is examined by the means of three central principles: 1) transparency, 2) accountability and 3) efficiency are analyzed from the organizational point of view. In the case of transparency the interest is focused on free information and the influence on organizational culture. Accountability is examined by the means of variety of term’s content. In the case of efficiency the interest is focused on decision-making and productivity. The nature of the study is qualitative; the study is focused on the matters like uniqueness and differences among the cases. The used material consists of both national and international literature as well as articles about good governance and the chosen principles; besides printed material I have used electronic resources like the home pages of relief organizations. In addition, the used material consists of the interviews of ten people in ten relief organizations in Finland. The crucial finding of the study is that the central principles of good governance seem to be taken commendably into account in the relief organizations. Still, one can find differences among principles. 1) Transparency seems to be the clearest principle in the organizations. Alongside with other information channels organizations utilize the possibilities of electronic tools by having home pages and intranet as well as using the e-mail lists in the communication with the donors, members and partners. However, the common regulations about organizations’ reporting seem to be needed. 2) Accountability is understood as responsible actions in the society where the financial point of view has to be taken into account, but is not the most crucial matter. Besides donors and partners organizations feel to be accountable to their customers. 3) Efficiency seems to be the most complex issue. Although organizations have found some proper indicators many of the cases it still seems to be challenging. It seems that relief organizations, as part of non-profit organizations, are professional actors whose working methods do not substantially differ from others sectors. However, the special aim and nature of relief organizations create a challenge how to measure the output in the most suitable way.
Keywords: goog governance; transparency; accountability; efficiency; relief organizations; fi=Hallintotiede : European Civil Servants - kansainvälisen hallinnon ohjelma|